2020
DOI: 10.1021/acssuschemeng.9b07552
|View full text |Cite
|
Sign up to set email alerts
|

Directing the Simultaneous Conversion of Hemicellulose and Cellulose in Raw Biomass to Lactic Acid

Abstract: The production of lactic acid (LaA) directly from actual biomass via a one-step reaction without pretreatment by chemocatalysis has shown high potential for satisfying its enormous demand in widespread applications. Here, we developed an integrated catalytic strategy using Y­(III) as the catalyst, enabling the simultaneous conversion of hemicellulose and cellulose components in the actual biomass and selectively yielding LaA with a yield up to 66.3%. The evaluated turnover frequency was 9.7 h–1, the highest va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…As biodiesel is produced on a large scale, the use of GL has become an important factor affecting the development of the biodiesel industry. GL can be converted into valuable chemicals by reaction, such as acrolein, 3 glycerol ether, 4 1,2-propanediol, 5 lactic acid, 6,7 and glycerol carbonate (GLC). 8 GLC is an important derivative of GL with a high boiling point, high biodegradability, low ammability, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…As biodiesel is produced on a large scale, the use of GL has become an important factor affecting the development of the biodiesel industry. GL can be converted into valuable chemicals by reaction, such as acrolein, 3 glycerol ether, 4 1,2-propanediol, 5 lactic acid, 6,7 and glycerol carbonate (GLC). 8 GLC is an important derivative of GL with a high boiling point, high biodegradability, low ammability, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, physical mixture of γ‐Al 2 O 3 with Y 2 O 3 as catalyst resulted in a substantially enhanced lactic acid yield of 63.7 % under identical conditions (Table 2, entry 7), which was far higher than that of the individual compound, suggesting that both Y 2 O 3 and γ‐Al 2 O 3 were the essential active sites for the efficient production of lactic acid from cellulose [16a] . As expected, the Y 2 O 3 /Al 2 O 3 gave significantly enhanced lactic acid yield than that of physical mixture of Y 2 O 3 and γ‐Al 2 O 3 , indicated that modification of Y on the γ‐Al 2 O 3 can efficiently inhibited the production of by‐product such as HMF, mainly due to generating new Lewis acid sites and Brønsted acid sites as a result of the interaction between yttrium species and γ‐Al 2 O 3 in internal catalyst, they were cooperative in promoting the hydrolysis of cellulose, isomerization of glucose, and the selective cleavage of C3‐C4 bond of soluble oligosaccharides via retro‐aldol condensation reaction, consequently leading to the formation of lactic acid [18b] . Besides, we intentionally reduced the content of Y with 5wt.…”
Section: Resultsmentioning
confidence: 99%
“…2 For example, monomers produced from various types of biomass can be used to synthesize degradable plastics, which beneficially reduces white matter pollution. 5-(Hydroxymethyl)furfural (5-HMF) is a vital platform molecule that can be used as a raw material to synthesize 2,5-furandicarboxylic acid, 3 2,5-bis(hydroxymethyl)furan, 4 dimethylfuran, 5 adipic acid, 6 hexanediol, 7 levulinic acid, 8 and other fine chemical raw materials. Biomass is the most economical feedstock for the production of 5-HMF.…”
Section: Introductionmentioning
confidence: 99%